Pengaruh Lingkungan Sekolah Terhadap Motivasi dan Minat Belajar Siswa Sekolah Dasar - Muhammad Ta’rifudin; Imas Mastoah (STKIP Subang, 2025)
The school environment often becomes an obstacle for students in the learning process. Learning involves efforts to stimulate students' motivation and interest in studying. Effective education must be able to create a supportive environment that fosters curiosity and enthusiasm for learning. Motivation and interest are psychological factors that play a crucial role in shaping students' engagement in the learning process, leading to better academic outcomes without coercion. A positive and conducive school environment is believed to significantly influence students’ academic achievement. This study aims to explore the extent to which the school environment affects the motivation, interest, and academic performance of elementary school students. The research method employed is a literature review, involving the analysis of relevant books and scholarly sources. The findings indicate a significant relationship between a supportive school environment and the improvement of students’ academic achievement, motivation, and interest in learning